The impact of teacher’s presence on learning basic surgical tasks with virtual reality headset among medical students - Sofianna Ojala; Joonas Sirola; Timo Nykopp; Heikki Kröger; Henrik Nuutinen (Medical Education Online, 2022)
Background The aim of this study was to investigate whether the presence of a teacher affects learning related outcomes in teaching basic surgical tasks with a Virtual Reality (VR) headset.Methods 26 fourth-year medical studentsparticipated in a voluntary exercise. Students practiced basic surgical procedure exercises using the VR4HEALTHCARE application in VR with OCULUS Rift S glasses. 12 students performed the exercises under the guidance of a teacher and 14 without the teacher present. After the exercise, the groups filled out a feedback form. Statistical analysis was performed using IBM SPSS Statistics 25.0 software using the Mann-Whitney U test and multivariate analysis of variance.Results The most important data collected related to whether the student learned something new and whether VR adds value to medical education. Ratings were based on a scale of 0–10 (0 = worst, 10 = best). When the teacher was present, on average, the students felt that they were learning something new and gave an average rating of 7.8 ± 1.8, and when the teacher was not present 5.3 ± 2.6 (p = 0.003). VR added value to teaching with a rating of 7.8 ± 1.7 when the teacher was present and 5.5 ± 3.0 when not present (p = 0.045). This study also analyzed specific use of VR for abscess incision, suturing and insertion of a suprapubic catheter.Discussion When a teacher was present VR added value to teaching and the usefulness and usability of VR was experienced more positively. The student should also have adequate knowledge of the subject to be taught before VR training.Conclusions VR adds value to teaching, but VR exercises may not completely replace high-quality traditional teaching methods. Consequently, it is important to determine the differences between VR and traditional teaching methods and how to combine these methods in the future.